Cryopreservation of Thyroid Primary Culture of Newborn Piglets - Bilyavskaya, S. B.; Ustichenko, V. D.; Bozhok, G. A.; Legach, E. I. (Problems of Cryobiology and Cryomedicine, 2011)
Effect of cryopreservation with the cooling rate of 1 degree/min and cryoprotective media based on dimethylsulfoxide (DMSO) solution on survival and viability indices of newborn piglets thyrocyte primary culture, represented by cell and follicular fractions was studied. The optimal concentrations of DMSO for cryopreservation of thyroid gland cells and follicles were established.